Effects of messenger molecule degradation in molecular communication via diffusion - Heren, Akif Cem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
Nanonetworking is a promising new paradigm that focuses on communication between nanoscale machines. In the nanonetworking literature, many solutions have been suggested to enable the information transfer between nano-machines. Among these solutions, we focus on molecular communication via di usion which constitutes a basis for many types of molecular communication. Speci cally, we start with the analytical model of 3-D absorbing receiver under messenger molecule degradation and show that our formulations are in agreement with the simulation results. Next, we identify the e ects of degradation in signal characteristics such as pulse peak time and pulse amplitude, and we analytically show how degradation is used for signal shaping in molecular communication via di usion. Here, we also compare communication under degradation with the case of no degradation and electromagnetic communication in terms of channel characteristics. Lastly, we evaluate the performance of the degradation system for di erent choices of degradation rates. Here, we assess the system performance according to traditional network metrics such as the level of inter-symbol interference, detection performance, bit error rate, and data rate. Our results indicate that introducing degradation signi cantly improves the system performance. For a given distance, increasing degradation rate also increases the system performance in terms of all metrics mentioned above up to a peak performance point. However, after the peak point, degradation becomes too fast and causes most of the molecules to degrade before reaching the receiver, which in turn deteriorates the system performance.
Keywords: Nanoelectronics.